O espaço psicoterápico na psicanálise freudiana e na abordagem centrada na pessoa: um estudo comparativo - Silva, Paulo Roberto Mattos da (1983)
Our dissertation deals with a comparative study between the Client-Centered Therapy and Psychoanalysis emphasizing mainly theoretical aspects related to clinical practice. CIient-Centered Therapy in presented by the ideas of its founder -Carl Rogers. We have given special attention to its basic assumptjons, but also to a theoretical structure which underlies a clinical practice with special characteristics Gendlin's contributions are also studied, ln order to reach a more complete understanding of the change process. Freud's ideas are presented mainly in terms of psycho – analytic treatment. At the same time, more recent developments are studied, with regard to psychoanalysis, purporting to give a broader view of this approach. We have undertaken a comparative analysis of psychotherapeutical modalities, with regard to its developmental characteristics. Issues on which they agree and disagree are pointed out, and we also tried to establish an exchange which could favour the practical efficiency of these models. The heuristic value of inter-theoretical investigations ln ratified. On the other hand, we emphasize the importance of a clinical endeavour in which the total personal resources of the therapist are considered, with regard o psychoanalysis as well as Client-Centered Therapy. Last but not least, we suggest that interrlates studies of culture, language and psychotherapeutic models qre decisive in order to enable us to reachea deeper understanding of psychological change.